Sexual Violence and Gender-Based Violence against Women and Girls in Iraq: Roots and Structural Causes - Hamadi, Dr. Ilham Maki (Thi Qar Arts Journal, 2023)
The plight of women and girls in Iraq predates the U.S-led invasion in 2003. Sexual and gender-based violence (SGBV) is strongly linked to the widespread use of violence within the country, be it in the state’s relationship with society or in relationships within society itself. Lawlessness and recurring armed conflicts have undermined the mechanisms in place for protecting women, which were already inadequate and unable to protect them in peacetime, amid a widespread ‘victim-blaming’ mentality. Conflicts in Iraq not only fostered an enabling environment for violence, but also saw various parties use SGBV against women and girls as a means for imposing political agendas and a justification for the destruction of their adversaries. Discrimination, a lack of gender equality and equity, and the stereotyping of gender roles in relation to family, society, and the law, are among the main factors that fuel the existence and persistence of sexual violence, both in peacetime and in war.Some forms of SGBV against women and girls that had, in general, been previously tolerated in Iraqi society have been criminalized in recent years. The heinous crimes committed by ISIS against women and girls in the vast areas under the group’s occupation raised international attention and were widely denounced. This led to increased documentation of sexual violence against women and girls, as evidenced by the monitoring of sexual violence crimes and violations in the reports of local organisations and local media outlets and news agencies. Nevertheless, efforts by Iraqi government institutions to document and categorise SGBV are wanting.Victims face stigma, blame, and discrimination by their families, society, and those working in referral system institutions, which further undermines access to justice, reparations, and protection. One of the main reason for the persistence of SGBV is the reluctance of victims and survivors to come forward and report these types of violations